Особливості експресії PSA структурами передміхурової залози людини - Попко, Світлана Сергіївна; Євтушенко, Валентина Михайлівна; Попко, С. С.; Евтушенко, В. М.; Popko, S. S.; Evtushenko, V. M. (Дніпро : [б. в.], 2018)
РЕФЕРАТ. Мета - дослідити імуногістохімічні особливості експресії PSA структурами передміхурової залози людини в пре- та постнатальний період онтогенеза. Об'єкт. Морфофункціональні особливості епітеліоцитів 65 передміхурових залоз людини у віці від 8 тижнів гестації до 75 років. Результати. Встановлено, що залозисті компоненти передміхурової залози досягають найбільшого морфофункціонального розквіту в період 20 - 35 років. Після 40 років в простаті зменшується кількість залозистих відділів з нормальною функцією. Зазначені зміни поступово прогресують і приводять в старечому віці до різкого наростання сполучної тканини, залозистих відділів і зниження маси гладком'язової тканини. Висновки. Протягом онтогенезу гістофункціональний стан передміхурової залоза змінюється в повній відповідності до вікових змін організму в цілому. Відхилення в нормальному співвідношенні паренхіматозних і стромальних компонентів можуть створити сприятливі умови для виникнення патологічних станів в передміхуровій залозі. РЕФЕРАТ. Цель - исследовать иммуногистохимические особенности экспрессии PSA структурами предстательной железы человека в пре- и постнатальном периоде онтогенеза. Объект. Морфофункциональные особенности эпителиоцитов 65 предстательных желез человека в возрасте от 8 недель гестации до 75 лет. Результат. Установлено, что железистые компоненты предстательной железы достигают наибольшего морфофункционального расцвета в период 20 - 35 лет. После 40 лет в простате уменьшается количество железистых отделов с нормальной функцией. Указанные изменения постепенно прогрессируют и приводят в старческом возрасте к резкому нарастанию соединительной ткани, железистых отделов и снижение массы гладкомышечной ткани. Выводы. На протяжении онтогенеза гистофункциональное состояние предстательной железы меняется в полном соответствии с возрастными изменениями организма в целом. Отклонения в нормальном соотношении паренхиматозных и стромальных компонентов могут создать благоприятные условия для развития патологических состояний в предстательной железе. ABSTRACT. Background. PSA - prostate-specific antigen is synthesized by the epithelium of the prostate and secreted into the seminal fluid, provides a more liquid consistency of sperm. PSA is a specific marker of glandular tissue of the prostate gland. PSA level is used for differential diagnosis of benign and malignant prostate gland diseases. In morphological studies, the immunohistochemical study of PSA expression reflects the degree of maturity and functional activity of the prostate glandular epithelium. An objective of the research: to study of immunohistochemical features of PSA expression by human prostate gland structures in the pre- and postnatal period of ontogenesis. Methods. An object of this study: 65 prostate glands of human aged of 8 weeks gestation to 75 years; using immunohistochemical method by determining the PSA expression (1:50) (DAKO). Results. The analysis made it possible to establish that the predominant component of the stroma of the prostate in prenatal ontogenesis is a loose fibrous connective tissue that performs important morphogenetic functions. Secretory sections appear, are lined with prismatic epithelium. However, there is a lack of PSA-expression by epithelial cells. Futher, in the prostate gland up to the age of five, one can observe a developed system of excretory ducts and secretory divisions. Between high cells there are small cells with intensely stained cytoplasm. In the cells of the glandular departments, a positive reaction of the PSA marker appears. In adolescence, profound morphological and functional changes occur in the glandular, connective tissue and lymphoid structures of the human prostate. In this age period, the most characteristic features of the second critical period of ontogenesis of the prostate are manifested most clearly. It present positive expression of the marker of PSA in cells of glandular epithelium of the human prostate. In the period from 17 to 36 years, there is an intensive increase in the parenchymal elements of the prostate gland, while decreasing the percentage of connective tissue components. As a rule, in the lumen of the excretory ducts and the secretory departments, groups of desquamated epithelial cells occur, and in some areas of the organ of prostatic nodule of various sizes. In the old age, signs of involutive restructuring are found, characterized by a decrease in the number of normally functioning glandular sections. As a result of atrophic changes in the glandular apparatus, the amount of fibrous tissue increases. Conclusion. Deviations in the normal ratio of parenchymal and stromal components can create favorable conditions for the appearance of pathological conditions in the prostate gland.
Особенности экспрессии PSA структурами предстательной желе-зы человека
Features of the PSA expression by human prostate gland structures
Keywords: передміхурова залоза; епітеліальний компонент; імуногістохімічний метод; простат-специфічний антиген; предстательная железа; эпителиальный компонент; иммуногистохимический метод; простат-специфический антиген; prostate gland; epithelial component; immunohistochemical method; prostate-specific antigen